2023
DOI: 10.1111/jsr.13873
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological evaluation of phenoconversion risk in REM sleep behaviour disorder: A scoping review

Abstract: SummaryThe objective of this study was to assess the role of cognitive evaluation in the prediction of phenoconversion in polysomnography‐confirmed idiopathic or isolated rapid eye movement sleep behaviour disorder, through a scoping review focussing on a longitudinal comprehensive neuropsychological assessment of patients with idiopathic REM sleep behaviour disorder. A literature search (2006–2022) yielded 1034 records, and 20 were selected for analysis. The sample included 899 patients from eight different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous studies showed that cognitive impairment can serve a potential biomarker of phenoconversionin iRBD and inclusion of cognitive assessment in standard evaluations of iRBD seems to be beneficial (de Natale et al., 2022 ; Wang et al., 2022 ). However further studies are needed to choose the type of test as well as to identify the criteria for defining mild cognitive impairment (MCI) (Fiamingo et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that cognitive impairment can serve a potential biomarker of phenoconversionin iRBD and inclusion of cognitive assessment in standard evaluations of iRBD seems to be beneficial (de Natale et al., 2022 ; Wang et al., 2022 ). However further studies are needed to choose the type of test as well as to identify the criteria for defining mild cognitive impairment (MCI) (Fiamingo et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%